IEAP Initiative Status Report Fall 2022 (2022)
Purpose: The Center for Community Engagement (CCE) seeks to continue to actively participate in retention efforts by expanding students' access to service-learning, volunteerism, and community service programs that prepare them to be socially responsible and civically engaged, therefore developing a greater sense of belonging in the university community. One way we are proposing to do this is by embedding service-learning into Ethnic Studies courses, a graduation requirement of the CSU, thereby having this high-impact practice available to more students.